Intellectual property rights protection and foreign direct investment: a study of BRICS countries. (2018) - Kumar, Rajender; Yadav, Sunil Kumar; Verma, Saurabh
Economic implications of intellectual property rights protection have always been a matter of debate among policy makers. It is assumed that FDI inflow in any nation depends upon the level of protection given to the creation of intellectual capital. Studies conducted on developed nations built strong link between IPR protection and foreign direct investment. The debate centred on whether these results can be reciprocated for developing countries. This study adds new dimensions to the existing literature by analysing the impact of IPR protection on FDI inflow in BRICS nations with the help of country specific data for the period of 2000-2015. FDI inflow is considered as dependent variable and charges of IP use, patent granted, patent filed by residents, non-residents and R&D expenditure as the percentage of GDP as an independent variable and proxy to IPR protection. The empirical results suggest that charges of IP use, total patent granted and patent filed by non-residents affects FDI inflow. Further study concludes that stronger IPR protection in developing countries will infuse foreign direct investment in the technology oriented knowledge sectors where probability of loss due to imitation is high.